P.015 Monthly migraine days, acute medication use-days, and migraine-specific quality of life in responders to atogepant: a post hoc analysis. (June 2022) - Dodick, DW; Lipton, RB; Nahas, SJ; Pozo-Rosich, P; McAllister, P; Mechtler, LL; Leroux, E; Ma, J; Dabruzzo, B; Dufek, M; Severt, L; Finnegan, M; et al.
Abstract : Background: In phase 3 ADVANCE, atogepant 60mg reduced mean monthly migraine days (MMDs) from 7.8 days (baseline) to 3.0 (weeks 9-12; Δ=−4.7) in the overall episodic migraine population [treatment responders and nonresponders (i.e., marked benefit and minimal benefit)], which obscures information regarding magnitude of treatment effect in these populations. Here, magnitude of treatment effect in atogepant responders and nonresponders is characterized. Methods: Mean MMDs, acute medication use-days (MUDs), and Migraine-Specific Quality of Life-Role Function-Restrictive (MSQ-RFR) scores were calculated in treatment responders (based on MMD percentage reduction) and nonresponders from ADVANCE participants. Results: From baseline to weeks 9-12, ≥50% improvement was achieved by 71% (139/195) of participants. In these responders, MMDs reduced from 7.6 to 1.3 (Δ=−6.3). 50% (97/195) of participants achieved ≥75% response. In this group, MMDs reduced from 7.7 to 0.6 (Δ=−7.1). Atogepant 60mg nonresponders (<25% reduction in MMDs; 15% [30/195 participants]) showed MMD change from 7.7 to 9.1 (Δ=+1.4). Acute MUDs in ≥50% MMD responders decreased 7.1 to 1.6 (Δ=−5.5). In treatment-nonresponders, acute MUDs were 7.3 (baseline) and 7.2 (weeks 9-12; Δ=−0.1). Similar mean MSQ-RFR score changes were observed in both populations. Conclusions: Of participants who experienced ≥50% reduction in MMDs, 71% had substantial treatment effect (ΔMMD=−6.3), representing 83% reduction in MMDs.